2004
DOI: 10.1002/ps.833
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal activity of vulgarone B against ram's horn snail (Planorbella trivolvis)

Abstract: The ram's horn snail (Planorbella trivolvis (Say)) is an intermediate host for a digenetic trematode (Bolbophorus confusus (Krause) Dubois) that has recently been discovered to be a significant problem in commercial channel catfish (Ictalurus punctatus Raf) production ponds in the Mississippi Delta region in the USA. In these catfish ponds, the digenetic life cycle of this parasitic trematode involves two intermediate hosts, the ram's horn snail and the channel catfish, and the final host, the American white p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…One of the bioactive components that is found in Artemisia spp. is vulgarone B, and this bioactive component, although not isolated and quantitatively determined in this study, is known to have molluscicidal activity [4,14]. Phytochemical tests of wormwood EE revealed the presence of tannins, saponins, and terpenoids.…”
Section: Discussionmentioning
confidence: 60%
“…One of the bioactive components that is found in Artemisia spp. is vulgarone B, and this bioactive component, although not isolated and quantitatively determined in this study, is known to have molluscicidal activity [4,14]. Phytochemical tests of wormwood EE revealed the presence of tannins, saponins, and terpenoids.…”
Section: Discussionmentioning
confidence: 60%
“…Vulgarone B is present at a concentration of 85% in the steam distillate of the aerial parts of the plant 10. In previous investigations we have demonstrated that vulgarone B possesses molluscicidal activity against ram's horn snail, Planobdella trivolvis (Say), a pest in commercial catfish production ponds in the mid‐south area,16 and against golden apple snail, a pest in rice paddies in Asian rice‐producing countries 17. We have also shown that vulgarone B exerts antifungal activity against some agriculturally important plant pathogenic fungi, namely Colletotrichum fragariae Brooks, Colletotrichum acutatum Simmonds, Colletotrichum gloeosporioides (Penz.)…”
Section: Resultsmentioning
confidence: 99%
“…Vulgarone B (Figure 8), isolated from the steam distillate of the aerial parts of the plant Artemisia douglasiana (Asteraceae), has been found to be active towards ram’s horns nails with an LC 50 of ca 24 µM [49]. This compound caused severe hemolysis associated with lethal activity to the snails at concentrations that were not toxic to channel catfish.…”
Section: Mollusc Managementmentioning
confidence: 99%